Marine Xanthones as Promising Phosphodiesterase-5 Inhibitors in the Management of Erectile Dysfunction: An In silico Approach - Do Tien, Lam; Thi, Thuy Phan; Xuan, Ha Nguyen; My, Chau Le Thi (Letters in Drug Design & Discovery, 2024)
ObjectivePhosphodiesterase-5 (PDE5) is an enzyme that promotes the degradation of cGMP in the blood, leading to a restriction in regulating blood flow in the penis, thereby reducing cGMP causing difficulties for men in achieving hardness (erectile dysfunction). Natural products with fewer side effects are being developed in many different treatment strategies and are necessary today. The current study aims to evaluate this enzyme's in silico inhibitory potential and marine xanthones through computational models.MethodsThe database of marine xanthones was collected from previously published literature. Protein structures were downloaded from the RCSB protein data bank (PDB ID: 1UDT). Molecular docking studies were performed using the AutoDock Vina v1.2.3 program to conduct screening. Molecular dynamics simulations were carried out with the GROMACS program to assess structural stability, and gmx_MMPBSA was used to make free-binding energy calculations for each PDE5 protein complex with potential compounds. Furthermore, Density Functional Theory (DFT) was applied in this study to calculate the atomic properties of the molecules based on quantum mechanics using the Gaussian 09 program.ResultsMolecular docking revealed that 21 compounds (staprexanthone A (69), emerixanthone E (89), emerixanthone A (90), emerixanthone C (91), varixanthone (92), aspergixanthone H (95), austocystin L (98), austocystin M (99), emerixanthone D (109), 15-acetyl tajixanthone hydrate (117), tajixanthone hydrate (118), 16-chlorotajixanthone (119), citreamicin ε A (131), citreamicin ε B (132), engyodontochone A (146), citreamicin θ B (151), citreaglycon A (152), dehydrocitreaglycon A (153), neocitreamicin I (159), citreamicin α (161), ukixanthomycin A (165) had superior binding affinities (ΔG < -11 kcal/mol) compared to the control inhibitor. Molecular dynamics confirmed the stability of the protein-ligand complexes. MM/GBSA analysis showed nine compounds (91, 98, 109, 118, 119, 151, 159, 161, 131) had binding energies comparable to or better than sildenafil. Quantum mechanical estimates indicated their potential as electron donors and acceptors, highlighting their antagonistic potential.ConclusionThese promising marine xanthones warrant further research to assess their PDE5 inhibitory activity in vitro and in vivo. This could provide valuable insights for developing new natural resource-based drugs to prevent or treat erectile dysfunction.
Keywords: marine xanthones